A Consumer Preferences in Culinary Tourism Fresh Tuna Fish Chest and Jaw Bones Case Study in Manado City, North Sulawesi Province - Longdong, Florence Verra; Tumbol, Reiny Antonetha; Aling, Djuwita R.R. (International journal of Horticulture, Agriculture and Food science, 2023)
The fishery products produced are not necessarily only for export purposes but are intended for national consumption. This research aims to analyze consumer preferences for processed fresh tuna products, namely the breast and jaw portions of tuna and identify consumer attitudes towards their choice of processed fresh tuna. The data in this research are primary data and secondary data. The sampling technique is based on purposive sampling and accidental sampling. Quantitative descriptive data analysis was carried out to analyze consumer attitude preferences. Based on the results of data processing between the menu attributes of tuna jaws and breasts, it turns out that consumers prefer tuna jaws compared to tuna breasts, the reason most likely lies in the sensation they get when eating tuna jaws. Even if asked about taste, both are equally tasty. The results obtained in this research show consumer preferences for tuna jaw and breast products on the food menu. Respondents preferred the processed Tuna Jaw menu where a utility (positive) value was obtained of 0.470 compared to the Tuna Breast menu with a utility (negative) of -0.470. In food variants, respondents preferred processed Burn Rica where the utility value was obtained at 3,690 compared to Woku at -0.642 and gravy at only -3,048. In the food price variable, respondents prefer food at a price of 50 thousand, where the utility value is 0.873 compared to the price of 45 thousand, the utility is 0.617, whereas at the price of 40 thousand it is only -0.995, and at the price of 60 thousand the utility value is -0.495, both of which are negative. The conclusion of this research is that consumer preferences for processed fresh tuna jaw and tuna breast fish products show that consumers prefer the processed Jaw Tuna menu where a utility value (positive) is obtained of 0.470 compared to the Tuna Breast menu with a utility (negative) of -0.470 .